2022
DOI: 10.1002/jmv.27762
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of interleukin‐38 levels in serum of patients with coronavirus disease 2019

Abstract: Interleukin‐38 (IL‐38) has recently been considered as a cytokine with anti‐inflammatory properties in viral respiratory infections, particularly coronavirus disease 19 (COVID‐19), but the evidence has not been well elucidated. Therefore, a case‐control study was conducted to determine IL‐38 serum levels in 148 patients with COVID‐19 (45 moderate, 55 severe, and 48 critical) and 113 controls. Results demonstrated that IL‐38 levels did not show significant differences between patients and controls (68.7 [interq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…IL-38 has been previously analyzed in serum of COVID-19 patients with some discrepancies. A study observed a negative correlation of IL-38 concentration with the severity of the disease ( 41 ), whereas a different study did not find any correlation of IL-38 with patient status ( 42 ). These differences might be associated with distinct parameters used to define disease severity, sample size and/or time point of plasma collection.…”
Section: Discussionmentioning
confidence: 90%
“…IL-38 has been previously analyzed in serum of COVID-19 patients with some discrepancies. A study observed a negative correlation of IL-38 concentration with the severity of the disease ( 41 ), whereas a different study did not find any correlation of IL-38 with patient status ( 42 ). These differences might be associated with distinct parameters used to define disease severity, sample size and/or time point of plasma collection.…”
Section: Discussionmentioning
confidence: 90%
“…However, this was not confirmed in the larger validation cohort and may be an accidental finding. 30 who have recently reported no differences in serum IL-38 concentrations between healthy subjects and patients, nor differences between patients with moderate, severe, or critical disease. Our data are also in agreement with a study on healthy subjects that reported stable IL-38 concentrations over the course of 1 year and unaffected IL-38 concentrations in experimental human endotoxemia, 28 and would imply that IL-38 concentrations are unaffected by COVID-19.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study demonstrated that circulating IL-38 levels were not affected by COVID-19, disease severity, age, sex, or comorbidity with chronic disease in each stratum, while obese patients showed lower IL-38 levels [5]. Otherwise, those parameters seem to have concurrent impacts on IL-38 levels, as female patients showed higher IL-38 levels than male patients in severe disease subgroups, and older patients showed higher IL-38 levels than patients <50 years old in critical disease subgroups [5]. Consistent with our studies, they showed that moderate disease patients tended to have higher IL-38 levels than severe or critical disease patients [5].…”
mentioning
confidence: 97%
“…Subsequently, IL-38 expression was found to be significantly increased in patients hospitalized with influenza A/B or SARS-CoV-2 infection, and its level was negatively correlated with disease severity [4]. A recent study demonstrated that circulating IL-38 levels were not affected by COVID-19, disease severity, age, sex, or comorbidity with chronic disease in each stratum, while obese patients showed lower IL-38 levels [5]. Otherwise, those parameters seem to have concurrent impacts on IL-38 levels, as female patients showed higher IL-38 levels than male patients in severe disease subgroups, and older patients showed higher IL-38 levels than patients <50 years old in critical disease subgroups [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation